Tarlov Cysts Misdiagnosed as Adnexal Masses in Pelvic Sonography: A Literature Review - Kim, Shengshu; Lee, Ho jun; Park, Joong Hyun; Kim, Taeyeon; Nam, Kiyeun (Frontiers in Medicine, 2020)
Introduction: A Tarlov cyst (TC) is a perineural cyst filled with cerebrospinal fluid that originates from the dorsal ganglion or the spinal posterior nerve root. TCs are usually asymptomatic and incidentally found in the sacral region. Endopelvic extension of TCs is uncommon and can be misdiagnosed as an adnexal mass on gynecological ultrasound imaging. Methods: We performed a search for all clinical studies of TCs that mimicked adnexal masses that had been published through October 12, 2020. We placed no restrictions on language or year of publication in our search, and we performed searches with the following keywords: perineural cyst, Tarlov cyst, sclerotherapy, management, and prognosis. We included all misdiagnosed cases or cases considered as adnexal masses on pelvic sonography. Results: We identified 21 cases of TCs mimicking adnexal masses and conducted a comprehensive analysis of these 21 cases to assess the epidemiology, symptoms, initial diagnoses, provisional ultrasound diagnoses, confirmative modalities, sizes, locations, treatments, and outcomes. The 21 cases included 16 symptomatic cases (76%) and 5 cases with incidental findings (24%), and the average patient age was 41.3 years. The initial diagnosis was performed with ultrasonography in all cases. The most frequent misdiagnosis was unspecified adnexal mass. Confirmative diagnostic modalities were MRI only (67%), CT only (5%), and both MRI and CT (28%). Treatments were surgery (33%), conservative treatment (19%), percutaneous intervention (5%), and alcohol sclerotherapy (5%). In two symptomatic cases misdiagnosed as pelvic masses, cystectomy was performed and leakage of cerebrospinal fluid occurred, necessitating repair of the leak. In one of the asymptomatic patients, cauda equina syndrome occurred after alcohol sclerotherapy for misdiagnosed TC. However, the patient improved with no neurologic deficit after 18 months of conservative treatment. Conclusion: The possibility of large TCs should be considered when assessing adnexal masses in sonography. Since TCs can masquerade as pelvic masses, they should be considered if the mass appears tubular/cystic or multilocular/multiseptate, does not move with respiration, and originates from the sacrum in sonography with or without neurologic symptoms. Accurate diagnosis can prevent medical mismanagement and reduce patient discomfort.